Pengembangan Aplikasi Kuis Interaktif Untuk Membantu Proses Evaluasi Hasil Belajar Peserta Didik SMK Negeri 2 Yogyakarta Berbasis Android - Rifaldi Iqbal Bachtiar; Nurkhamid (Department of Electronics and Informatics Engineering Education, 2023)
The purpose of this research are: (1) Developing an android-based quiz application as a media evaluation assessment in learning implementation activities, (2) Testing application quality standards according to ISO 25010 with the characteristics of functional suitability, usability, compatibility, and performance efficiency. The method used is Research and Development (R&D) with the Rational Unified Process (RUP) application development procedure which consists of 4 phases, inception, elaboration, construction, and transition The results of this research are (1) Android application